SENSITIFITAS UDANG Litopenaeus stylirostris DAN Penaeus monodon TERHADAP INFEKSI SEMBV (SYSTEMIC ECTODERMAL AND MESODERMAL BACULOVIRUS) - A. Taslihan; R. Handayani; Suryati Suryati; N. Fahris (Jurnal Perikanan Universitas Gadjah Mada, 2002)
Study on sensitifity of two shrimps species, there were blue shrimp (Litopenaeus stylirostris) and giant tiger shrimp (Penaeus monodon) against local isolat of SEMBV (systemic ectodermal and mesodermal baculovirus) has been undertaken. The objective of  the study were to know sensitivity level of the two shrimp species to virus that cause serious disease namely WSDV (white spots disease virus). Result from the study showed that both shrimps are sensitive to the virus. Inoculating virus through injection caused  transmission faster than that by feeding shrimp with infected carcass. Blue shrimp also showed relatively sensitive to SEMBV then that of giant tiger prawn.